Meta-analysis of chemotherapy in nasopharynx carcinoma (MAC-NPC): An update on 26 trials and 7080 patients. (January 2022) - Blanchard, Pierre; Lee, Anne W.M.; Carmel, Alexandra; Wai Tong, Ng; Ma, Jun; Chan, Anthony T.C.; Hong, Ruey Long; Chen, Ming-Yuan; Chen, Lei; Li, Wen-Fei; Huang, Pei-Yu; Kwong, Dora L.W.; et al.
Highlights: Individual patient data meta-analysis including 26 trials and 7, 080 patients with locally advanced nasopharyngeal carcinoma. Addition of chemotherapy reduced the risk of death with an absolute survival increase at 5 and 10 years of 6.1% and 8.4% The benefit of chemotherapy was also demonstrated by improvements in progression-free survival, cancer mortality, locoregional control and distant control. The largest effect was observed for concomitant + adjuvant, induction (with concomitant in both arms) and concomitant chemotherapy. Chemotherapy benefit decreased with increasing patient age. Abstract: Purpose: Chemotherapy, when added to radiotherapy, improves survival in locally advanced nasopharyngeal carcinoma (NPC). This article presents the second update of the Meta-Analysis of Chemotherapy in NPC. Methods: Published or unpublished randomized trials assessing radiotherapy (±a second chemotherapy timing) with/without chemotherapy in non-metastatic NPC patients were identified. Updated data were sought for studies included in the previous rounds of the meta-analysis. The primary endpoint was overall survival. All trials were analyzed following the intent-to-treat principle using a fixed-effects model. Treatments were classified in five subsets according to chemotherapy timing. The statistical analysis plan was pre-specified. Results: Eighteen new trials were identified. Individual patient data were available for seven. In total, the meta-analysis now included 26 trials and 7, 080 patients. The addition of chemotherapy reduced the risk of death, with a hazard ratio (HR) of 0.79 (95% confidence interval (CI) [0.73; 0.85]), and an absolute survival increase at 5 and 10 years of 6.1% [+3.9; +8.3] and + 8.4% [+5.7; +11.1], respectively. The largest effect was observed for concomitant + adjuvant, induction (with concomitant in both arms) and concomitant chemotherapy, with respective HR [95%CI] of 0.68 [0.59; 0.79] (absolute survival increase at 5 years: 12.3% (7.0%;17.6%)), 0.73 [0.63; 0.86] (6.0% (2.5%;9.5%)) and 0.81 [0.70; 0.92] (5.2% (0.8%;9.6%)). The benefit of chemotherapy was also demonstrated by improvement in progression-free survival, cancer mortality, locoregional control and distant control. There was a significant interaction between patient age and chemotherapy effect. Conclusion: This updated meta-analysis confirms the benefit of concomitant chemotherapy and concomitant + adjuvant chemotherapy, and suggests that addition of induction or adjuvant chemotherapy to concomitant chemotherapy improves tumor control and survival. The benefit of chemotherapy decreases with increasing patient age.